Structural Characters and Pharmacological Activity of Protopanaxadiol-Type Saponins and Protopanaxatriol-Type Saponins from Ginseng - Lancao Zhang; Xiang Gao; Chunhui Yang; Zuguo Liang; Dongsong Guan; Tongyi Yuan; Wenxiu Qi; Daqing Zhao; Xiangyan Li; Haisi Dong; He Zhang (Advances in Pharmacological and Pharmaceutical Sciences)
Ginseng has a long history of drug application in China, which can treat various diseases and achieve significant efficacy. Ginsenosides have always been deemed important ingredients for pharmacological activities. Based on the structural characteristics of steroidal saponins, ginsenosides are mainly divided into protopanaxadiol-type saponins (PDS, mainly including Rb1, Rb2, Rd, Rc, Rh2, CK, and PPD) and protopanaxatriol-type saponins (PTS, mainly including Re, R1, Rg1, Rh1, Rf, and PPT). The structure differences between PDS and PTS result in the differences of pharmacological activities. This paper provides an overview of PDS and PTS, mainly focusing on their chemical profile, pharmacokinetics, hydrolytic metabolism, and pharmacological activities including antioxidant, antifatigue, antiaging, immunodulation, antitumor, cardiovascular protection, neuroprotection, and antidiabetes. It is intended to contribute to an in-depth study of the relationship between PDS and PTS.